Phylogeny and taxonomic review of Oreocomopsis with description of a new genus Oreocomoides (Apioideae, Apiaceae) - Kljuykov, Eugene; Lavrova, Tatiana; Terentieva, Elena; Ukrainskaja, Uliana; Zakharova, Ekaterina (Phytotaxa, 2023)
A revision of the genus Oreocomopsis was carried out based on the study of morphological, anatomical and molecular phylogenetic data based on ITS nrDNA sequences, of which the scope and composition were specified. The identity of O. xizangensis with the previously described O. dochenensis is shown; on the contrary, O. aromatica is singled out as an independent taxon. Ostericum scaberulum var. longiinvolucellatum is included in the genus Oreocomopsis as an independent species. Taxonomic features of the genus and differences from related genera are analysed. The species Oreocomopsis stelliphora has been assigned to the new genus Oreocomoides. The new genus Oreocomoides markedly differs from Oreocomopsis in many morphological characters, such as heterophyllous leaf blades: bipinnate in lower part and narrow-linear pinnate in upper part; bracts polymorphic, linear or pinnate with linear lobules; calyx teeth developed; petals with oval plate, at base with well-developed claw; pedicels rounded; mericarps ribs similar, narrowly-winged, slightly widened at the base.